Unlocking prosperity: The National Potato Strategy for Nigeria - CGIAR (International Potato Center, 2023)
October 2023 (Jos Plateau, Nigeria) The National Potato Strategy for Nigeria was launched to usher in a new era for Nigeria’s potato industry capable of delivering sustainable food and nutrition security, fostering trade surplus, and boosting incomes.